2010
DOI: 10.1007/s13197-010-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of the root extract of Decalepis hamiltonii against stored-product insect pests and its application in grain protection

Abstract: Root extracts of Decalepis hamiltonii were tested for insecticidal activity against the stored products pests, Rhyzopertha domonica, Sitophilus oryzae, Stigobium pancieum, Tribolium castaneum and Callosobruchus chinensis, in residual and contact toxicity bioassays. Methanolic extract showed LC50 value of 0.14 mg/cm(2) for all the test species in a filter paper residual bioassay. The extract was effective as a grain protectant for wheat and green gram. Reduction of F1 progeny was observed in treated grain store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 26 publications
0
39
1
Order By: Relevance
“…The damage to stored food products caused by insects accounts for about 5-10 % in the temperate regions of the world and 20-30 % in the tropical countries (Rajashekar et al 2010;Nakakita 1998). Management of these stored product insect pests mainly involves the use of synthetic pesticides in the form of fumigants and as residual contact insecticides (Devi and Devi 2013;Jaya et al 2012;Pandey et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The damage to stored food products caused by insects accounts for about 5-10 % in the temperate regions of the world and 20-30 % in the tropical countries (Rajashekar et al 2010;Nakakita 1998). Management of these stored product insect pests mainly involves the use of synthetic pesticides in the form of fumigants and as residual contact insecticides (Devi and Devi 2013;Jaya et al 2012;Pandey et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the implications of these on the health and environment have revived interest in the development of 'safer compounds' as grain protectants using the knowledge base of plants. (George et al 1999;Rajendran andSriranjini 2008 andRajashekar et al 2010) The essential oils of some spices are reported to exhibit insecticidal activity, (Owolabi et al 2009). However, knowledge on their application as insecticidal, antifeedant or antiovipositional agent is limited.…”
Section: Introductionmentioning
confidence: 99%
“…4 tonnes/ha (Anonymous, 2015a); out of which loss due to insect pests is about 26% as shown in figure 1 (Anonymous, 2015b) and food grain accounts for 20-25% damage by storage insect pests (Rajashekar et al, 2010) which is really a brainstorming matter. Among various storage insect pests Angoumois grain moth (Sitotroga cerealella), maize/ rice weevil (Sitophilus oryzae), lesser grain borer (Rhyzopertha dominica), khapra beetle (Trogoderma granarium), rust-red flour beetle (Tribolium castaneum), legume weevil (Callosobruchus sp.)…”
Section: Issn: 2319-7706 Volume 6 Number 6 (2017) Pp 1583-1594mentioning
confidence: 99%